Self-heating prefabricated component splicing adhesive and preparation method thereof

By introducing self-heating components into the epoxy resin-based prefabricated component splicing glue, and using the oxidative exothermic reaction of the heating agent, the problem of difficult curing of the epoxy resin-based splicing glue in a low temperature environment is solved, and curing and strength improvements are achieved below -5°C.

CN118667492BActive Publication Date: 2025-04-04KEHUI (HENAN) NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410967889.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-04-04
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

The existing epoxy resin-based prefabricated component splicing glue is difficult to cure below -5℃, resulting in limited construction progress in the northeast or northwest regions.

Method used

Self-heating prefabricated component splicing glue is used, which consists of isolated and stored components A and B. Component A contains a heating agent, component B contains a conductive agent and Class II thixotropic agent. When components A and B are mixed, the heating agent induces the reaction of epoxy resin and curing agent through oxidative exothermic reaction to achieve curing.

Benefits of technology

In a low temperature environment below -5°C, self-heating splicing glue can be cured, improving the reactivity and strength of splicing glue, and ensuring the safety and stability of prefabricated components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004952260860000041
    Figure BDA0004952260860000041
  • Figure BDA0004952260860000051
    Figure BDA0004952260860000051
  • Figure BDA0004952260860000061
    Figure BDA0004952260860000061
Patent Text Reader

Abstract

The present invention belongs to the field of building materials, and specifically relates to a self-heating prefabricated component splicing adhesive and a preparation method thereof. The splicing adhesive is composed of two components, A and B; wherein component A is composed of the following raw materials in parts by weight: 80 to 120 parts of epoxy resin, 1 to 20 parts of active diluent, 1 to 10 parts of liquid toughening agent, 5 to 30 parts of solid toughening agent, 1 to 10 parts of coupling agent, 50 to 200 parts of filler, 5 to 20 parts of heating agent, and 1 to 5 parts of Class I thixotropic agent; component B is composed of the following raw materials in parts by weight: 80 to 120 parts of curing agent, 1 to 10 parts of accelerator, 10 to 70 parts of Class II thixotropic agent, 0.1 to 5 parts of conductive agent, and 50 to 200 parts of filler. The self-heating prefabricated component splicing adhesive provided by the present invention can maintain high reactivity, high bonding strength and good toughness in a low temperature environment (-5°C to -25°C), and can be used for splicing various concrete prefabricated components and repairing concrete cracks in a low temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and in particular relates to a self-heating prefabricated component splicing adhesive and a preparation method thereof. Background Art

[0002] Prefabricated component splicing glue is usually epoxy resin-based material. Epoxy resin materials have high modulus, high strength, high adhesion, fatigue resistance, creep resistance and other properties, but they also have significant disadvantages, such as high brittleness, low toughness, and difficulty in solidification at ambient temperatures below -5°C, which makes it impossible to construct in winter. These shortcomings directly restrict the progress of wind power concrete tower splicing, bridge prefabricated component splicing, and joint rapid repair projects in Northeast or Northwest my country, making these projects unable to start or progress slowly during long low temperature periods.

[0003] There is no clear solution to the problem that epoxy resin splicing glue is difficult to cure below -5°C. Chinese patent CN117551409A discloses a room temperature curing ultra-low temperature resistant epoxy adhesive and its preparation method, providing an epoxy adhesive that cures at room temperature and has the characteristics of ultra-low temperature resistance, but still does not solve the technical problem of curing splicing glue under low temperature conditions. Summary of the invention

[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide a self-heating prefabricated component splicing adhesive and a preparation method thereof.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] A first aspect of the present invention provides a self-heating prefabricated component splicing adhesive, the splicing adhesive consisting of two components A and B stored in isolation;

[0007] The component A is composed of the following raw materials in parts by weight: 80-120 parts of epoxy resin, 1-20 parts of active diluent, 1-10 parts of liquid toughening agent, 5-30 parts of solid toughening agent, 1-10 parts of coupling agent, 50-200 parts of filler, 5-20 parts of heating agent, and 1-5 parts of Class I thixotropic agent;

[0008] The component B is composed of the following raw materials in parts by weight: 80-120 parts of a curing agent, 1-10 parts of an accelerator, 10-70 parts of a type II thixotropic agent, 0.1-5 parts of a conductive agent, and 50-200 parts of a filler.

[0009] Preferably, the splicing adhesive consists of components A and B in a weight ratio of (1-5):1.

[0010] Preferably, the component A is composed of the following raw materials in parts by weight: 100 parts of epoxy resin, 10 parts of active diluent, 5 parts of liquid toughening agent, 25 parts of solid toughening agent, 3 parts of coupling agent, 134 parts of filler, 20 parts of exothermic agent, and 3 parts of Class I thixotropic agent.

[0011] Preferably, the component B is composed of the following raw materials in parts by weight: 100 parts of curing agent, 5 parts of accelerator, 30 parts of type II thixotropic agent, 1 part of conductive agent, and 164 parts of filler.

[0012] Preferably, the epoxy resin is at least one of bisphenol A epoxy resin and bisphenol F epoxy resin.

[0013] More preferably, the epoxy value of the bisphenol A epoxy resin is 0.51-0.55 mol / 100 g; the epoxy value of the bisphenol F epoxy resin is 0.44-0.55 mol / 100 g.

[0014] Preferably, the active diluent is at least one of butyl glycidyl ether, 1,4-butanediol diglycidyl ether, benzyl glycidyl ether, dodecanediol glycidyl ether, and 1,6-hexanediol diglycidyl ether.

[0015] Preferably, the liquid toughening agent is at least one of carboxyl-terminated liquid nitrile rubber (CTBN), liquid polysulfide rubber, and hydroxyl-terminated liquid silicone rubber.

[0016] Preferably, the solid toughening agent is any one of ceramic whiskers and inorganic salt whiskers, or a mixture of the two.

[0017] More preferably, the ceramic whiskers are at least one of silicon carbide whiskers, potassium titanate whiskers, and aluminum borate whiskers; and the inorganic salt whiskers are at least one of calcium sulfate whiskers and calcium carbonate whiskers.

[0018] Preferably, the coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, anilinemethyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidoxytrimethylsilane, and γ-methacryloyloxypropyltrimethylsilane.

[0019] Preferably, the filler is at least one of quartz powder, talc, titanium dioxide, barium sulfate, calcium sulfate, calcium carbonate and aluminum oxide.

[0020] More preferably, the mesh size of the filler is 100-400 meshes.

[0021] Preferably, the heat-generating agent is iron powder, tungsten powder or a mixture of the two.

[0022] More preferably, the mesh size of the exothermic agent is 300-400 meshes.

[0023] Preferably, the type I thixotropic agent is hydrophobic fumed silica.

[0024] Preferably, the curing agent is at least one of an aliphatic polyamine curing agent, an aromatic polyamine curing agent, an alicyclic polyamine curing agent, and a modified polyamine curing agent.

[0025] Preferably, the accelerator is a tertiary amine accelerator.

[0026] More preferably, the tertiary amine accelerator is at least one of 2,4,6-tris(dimethylaminomethyl)phenol and 1,8-diazabicycloundec-7-ene.

[0027] Preferably, the type II thixotropic agent is any one of sodium bentonite and attapulgite, or a mixture of the two.

[0028] More preferably, the water content of the type II thixotropic agent is 10% to 20%.

[0029] Preferably, the conductive agent is at least one of sodium chloride, potassium chloride, sodium carbonate and potassium carbonate.

[0030] The second aspect of the present invention provides a method for preparing the self-heating prefabricated component splicing adhesive according to the first aspect, comprising the following steps:

[0031] (1) Preparation of component A: Mix epoxy resin, active diluent and liquid toughening agent evenly; add filler, solid toughening agent and coupling agent, and stir in vacuum; add exothermic agent and type I thixotropic agent, and stir evenly to obtain component A;

[0032] (2) Preparation of component B: Mix the curing agent and the accelerator evenly; add the filler and the conductive agent, and stir in a vacuum; add the type II thixotropic agent, and stir evenly to obtain component B.

[0033] Step (3), when in use, mix component A and component B evenly to obtain the splicing glue.

[0034] Preferably, the epoxy resin, the active diluent and the liquid toughening agent are placed in a stirring kettle and mixed. The stirring kettle is preheated before mixing. The preheating temperature is 60° C. to 90° C. and the mixing time is 5 min to 30 min.

[0035] Preferably, the vacuum stirring time is 30 min to 60 min.

[0036] The beneficial effects of the present invention are:

[0037] (1) The present invention proposes a method of improving the toughness of splicing adhesive by blending a liquid toughening agent and a solid toughening agent. In particular, when micron-sized whiskers are selected as solid toughening agents, they can be interspersed in epoxy resin, thereby improving the toughness of the splicing adhesive and making it less prone to brittle cracking. In addition, they can be used as reinforcing agents to improve the strength of the splicing adhesive.

[0038] (2) The present invention evacuates component A for dehydration, then adds a coupling agent to form a hydrophobic system, and finally adds a heat-generating agent for sealed storage, so that the heat-generating agent is difficult to react under normal conditions, and will only start to react when it encounters component B. After components A and B are mixed in proportion, the heat-generating agent uses the air brought by the mixing process and the moisture and conductive agent brought by component B to generate oxidation heat, inducing the epoxy resin and the curing agent to start reacting, so that it can be cured in an external environment below -5°C, achieving the expected mechanical properties, and improving the safety of prefabricated components.

[0039] (3) The epoxy resin and curing agent release heat during the reaction process, which not only promotes their own reaction, but also accelerates the dehydration of the Type II thixotropic agent in component B, providing moisture for the exothermic agent until the oxygen in the mixture is exhausted and the exothermic agent stops reacting. In addition, the exothermic agent becomes an oxide after the reaction, and its volume increases, which occupies the original air space and makes the overall structure more compact. DETAILED DESCRIPTION

[0040] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0041] The invention provides a self-heating prefabricated component splicing adhesive, which is composed of two components A and B stored in isolation according to a weight ratio of (1-5):1.

[0042] The component A is composed of the following raw materials in parts by weight: 80-120 parts of epoxy resin, 1-20 parts of active diluent, 1-10 parts of liquid toughening agent, 5-30 parts of solid toughening agent, 1-10 parts of coupling agent, 50-200 parts of filler, 5-20 parts of heating agent, and 1-5 parts of Class I thixotropic agent;

[0043] The component B is composed of the following raw materials in parts by weight: 80-120 parts of a curing agent, 1-10 parts of an accelerator, 10-70 parts of a type II thixotropic agent, 0.1-5 parts of a conductive agent, and 50-200 parts of a filler.

[0044] The epoxy resin is at least one of bisphenol A epoxy resin and bisphenol F epoxy resin; the epoxy value of bisphenol A epoxy resin is 0.51-0.55 mol / 100g, and the epoxy value of bisphenol F epoxy resin is 0.44-0.55 mol / 100g. The active diluent is at least one of butyl glycidyl ether, 1,4-butanediol diglycidyl ether, benzyl glycidyl ether, dodecadecyl glycidyl ether, and 1,6-hexanediol diglycidyl ether. The liquid toughening agent is at least one of carboxyl-terminated liquid nitrile rubber (CTBN), liquid polysulfide rubber, and hydroxyl-terminated liquid silicone rubber. The solid toughening agent is any one of ceramic whiskers and inorganic salt whiskers or a mixture of two of them; the ceramic whiskers are at least one of silicon carbide whiskers, potassium titanate whiskers, and aluminum borate whiskers, and the inorganic salt whiskers are at least one of calcium sulfate whiskers and calcium carbonate whiskers. The coupling agent is at least one of 3-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, aniline methyl triethoxysilane, γ-(methacryloyloxy)propyl trimethoxysilane, N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane, γ-glycidoxy trimethylsilane, and γ-methacryloyloxypropyl trimethylsilane. The filler is at least one of quartz powder, talcum powder, titanium dioxide, barium sulfate, calcium sulfate, calcium carbonate, and aluminum oxide; the filler mesh number is 100 to 400 meshes. The exothermic agent is any one of iron powder and tungsten powder or a mixture of two; the exothermic agent has a mesh number of 300 to 400 meshes. The Class I thixotropic agent is fumed silica. The curing agent is at least one of an aliphatic polyamine curing agent, an aromatic polyamine curing agent, an alicyclic polyamine curing agent, or a modified polyamine curing agent of the curing agent. The accelerator is a tertiary amine accelerator, including at least one of 2,4,6-tris(dimethylaminomethyl)phenol and 1,8-diazabicycloundec-7-ene. The Class II thixotropic agent is any one of sodium bentonite and attapulgite or a mixture of the two; the moisture content of the sodium bentonite and attapulgite is 10% to 20%. The conductive agent is at least one of sodium chloride, potassium chloride, sodium carbonate and potassium carbonate.

[0045] The purchase information of some raw materials in the embodiment of the present invention is shown in Table 1:

[0046] Table 1 Part of the raw material purchase information

[0047]

[0048]

[0049] The present invention also provides a method for preparing the self-heating prefabricated component splicing adhesive, comprising the following steps:

[0050] (1) Preparation of component A:

[0051] S1: Weigh the raw materials according to weight, pour the epoxy resin, active diluent and liquid toughening agent into a double planetary stirring kettle preheated at 60°C to 90°C, and mix and stir for 5min to 30min;

[0052] S2: Add filler and solid toughening agent, and stir under vacuum for 30 to 60 minutes;

[0053] S3: Add coupling agent, vacuum and stir for 30min to 60min; pass cooling water to cool the liquid to room temperature;

[0054] S4: Add the heating agent and the type I thixotropic agent, stir evenly, and obtain component A;

[0055] (2) Preparation of component B:

[0056] S5: Weigh each raw material by weight, pour the curing agent and accelerator into a double planetary stirring kettle at room temperature, and mix and stir for 5 minutes to 30 minutes;

[0057] S6: Add filler and conductive agent, vacuum and stir for 30min to 60min;

[0058] S7: Add Type II thixotropic agent and stir evenly to obtain component B.

[0059] When in use, component A and component B are mixed according to a weight ratio and stirred evenly to obtain the prefabricated component splicing adhesive.

[0060] Example 1: Study on the effect of curing temperature on the performance of splicing adhesive

[0061] A prefabricated component splicing adhesive consists of two components A and B stored separately in a weight ratio of 3:1.

[0062] The component A is composed of the following raw materials in parts by weight: 80 parts of epoxy resin NPEL-128, 5 parts of active diluent XY501, 5 parts of coupling agent KBM-403, 2 parts of liquid toughening agent, 20 parts of solid toughening agent, 186 parts of filler, and 2 parts of Class I thixotropic agent H20; no exothermic agent is added.

[0063] The component B is composed of the following raw materials in parts by weight: 80 parts of curing agent 602, 3 parts of accelerator K54, 177 parts of filler, and 40 parts of type II thixotropic agent attapulgite.

[0064] The solid toughening agent is a mixture of 10 parts by weight of HM001 and 10 parts by weight of BS01; the filler in component A is a mixture of 160 parts by weight of quartz powder and 26 parts by weight of barium sulfate; the filler in component B is a mixture of 170 parts by weight of quartz powder and 7 parts by weight of calcium carbonate.

[0065] At different ambient temperatures, mix component A and component B according to the weight ratio, stir evenly, and pour into the corresponding test mold. Place the mold in the corresponding temperature for curing. The ambient cycle temperature (curing temperature) is set to -5°C to -25°C, 10°C, 23°C, and 35°C, respectively, and then refer to T / CECS10080-2020 "Epoxy Adhesive for Prefabricated Segment Assembly" to determine the compressive strength of the prefabricated component splicing glue provided by the present invention. Refer to GB / T 2567-2021 "Test Method for Performance of Resin Casting Body" to determine the flexural strength of the prefabricated component splicing glue provided by the present invention. The test results of compressive strength and flexural strength are shown in Table 2, respectively.

[0066] Table 2 Compressive strength and bending strength test results of Examples 1.1 to 1.4

[0067]

[0068] As can be seen from Table 2, the ambient temperature has a great influence on the strength of the splicing adhesive. The higher the temperature, the faster the reaction speed, and the shorter the time to reach the final compression strength and bending strength; on the contrary, as the temperature decreases, the reaction activity decreases significantly, and the rising trend of compression strength and bending strength slows down significantly. When the temperature is lower than -5℃, the increase rate of compression strength and bending strength is too slow, which does not meet the requirements of on-site splicing and often requires shutdown.

[0069] Example 2: Study on the effect of epoxy resin type on splicing adhesive performance under ultra-low temperature environment

[0070] Example 2.1

[0071] A prefabricated component splicing adhesive consists of two components A and B stored separately in a weight ratio of 2:1.

[0072] The component A is composed of the following raw materials in parts by weight: 120 parts of epoxy resin NPEL-128, 15 parts of active diluent XY692, 10 parts of coupling agent KBM-603, 10 parts of liquid toughening agent JLY-124, 10 parts of solid toughening agent HM001, 130 parts of filler, and 5 parts of Class I thixotropic agent H18;

[0073] The component B is composed of the following raw materials in parts by weight: 120 parts of curing agent HB-1808, 10 parts of accelerator DMP-30, 100 parts of filler, and 70 parts of type II thixotropic agent sodium bentonite.

[0074] The filler in the component A is a mixture of 100 parts by weight of quartz powder and 30 parts by weight of barium sulfate; the filler in the component B is a mixture of 80 parts by weight of quartz powder and 20 parts by weight of calcium carbonate.

[0075] At an ambient temperature of -5℃ to -25℃, mix component A and component B at a weight ratio of 2:1 and stir evenly, then pour into the corresponding test mold. Place the mold in the corresponding temperature for curing. The test results of compressive strength and flexural strength are shown in Table 3 and Table 4, respectively.

[0076] Examples 2.2 to 2.5

[0077] The contents of Examples 2.2 to 2.5 are exactly the same as those of Example 2.1, except that the types and proportions of resins in Examples 2.2, 2.3, 2.4 and 2.5 are different. The specific results are shown in Table 3.

[0078] Table 3 Compressive strength and bending strength test results of Examples 2.1 to 2.5

[0079]

[0080] As can be seen from Table 3, in an ultra-low temperature environment, changing the type and ratio of epoxy resin has no significant effect on the strength improvement. In a smaller strength variation range, it is found that the resin ratio (1:3) of Example 2.4 is better than the others.

[0081] Example 3: Study on the effect of curing agent type and dosage on the performance of splicing adhesive under ultra-low temperature environment

[0082] Example 3.1

[0083] A prefabricated component splicing adhesive consists of two components A and B stored separately in a weight ratio of 1:1.

[0084] The component A is composed of the following raw materials in parts by weight: 100 parts of epoxy resin, 10 parts of active diluent, 3 parts of coupling agent, 5 parts of liquid toughening agent, 25 parts of solid toughening agent, 154 parts of filler, and 3 parts of type I thixotropic agent; no exothermic agent is added.

[0085] The component B is composed of the following raw materials in parts by weight: 100 parts of curing agent, 5 parts of accelerator, 165 parts of filler, and 30 parts of type II thixotropic agent.

[0086] The epoxy resin is a mixture of 25 parts by weight of NPEL-128 and 75 parts by weight of NPEF-170; the active diluent is XY692; the coupling agent is KBM-603; the filler in component A is a mixture of 100 parts by weight of quartz powder, 30 parts by weight of barium sulfate and 24 parts by weight of aluminum oxide; the type I thixotropic agent is H18; the curing agent is GLC-905; the accelerator is DMP-30; the filler in component B is a mixture of 100 parts by weight of quartz powder and 65 parts by weight of calcium carbonate. The type II thixotropic agent is sodium bentonite.

[0087] Curing temperature: -5℃~-25℃.

[0088] Examples 3.2 to 3.6

[0089] The contents of Examples 3.2 to 3.6 are exactly the same as those of Example 3.1, except that the types of curing agents and the weight ratios of the A / B components in Examples 3.2, 3.3, 3.4, 3.5 and 3.6 are different.

[0090] At an ambient temperature of -5°C, mix component A and component B according to the weight ratio, stir evenly, and pour into the corresponding test mold. Place the mold in the corresponding temperature for curing.

[0091] The compressive strength of the prefabricated component splicing adhesive provided by the present invention was measured with reference to T / CECS10080-2020 "Epoxy Adhesive for Prefabricated Segment Assembly". The flexural strength of the prefabricated component splicing adhesive provided by the present invention was measured with reference to GB / T 2567-2021 "Test Method for Properties of Resin Castings". The test results of compressive strength and flexural strength are shown in Table 4, respectively.

[0092] Table 4 Compressive strength and bending strength test results of Examples 3.1 to 3.6

[0093]

[0094] As can be seen from Table 4, in the ultra-low temperature environment, without adding additional exothermic agent, the use of different curing agents has no significant effect on the strength improvement. In a smaller strength change range, there is a synergistic effect when the mixed curing agent HB-1808: Ancamine2636 = 30:70 is used, and the test results are better than using it alone.

[0095] Example 4: Study on the effect of the type and weight of the heating agent on the performance of the splicing adhesive

[0096] Example 4.1

[0097] A self-heating prefabricated component splicing adhesive is composed of two components A and B stored in isolation at a weight ratio of 2:1.

[0098] The component A is composed of the following raw materials in parts by weight: 100 parts of epoxy resin (mixed with 25 parts by weight of NPEL-128 and 75 parts by weight of NPEF-170), 10 parts of active diluent XY692, 3 parts of coupling agent KBM-603, 5 parts of liquid toughening agent, 25 parts of solid toughening agent, 134 parts of filler, 3 parts of Class I thixotropic agent H18, and 20 parts of heating agent iron powder;

[0099] The component B is composed of the following raw materials in parts by weight: 100 parts of curing agent (HB-1808: Ancamine2636 mixed at a ratio of 30:70), 5 parts of accelerator DMP-30, 164 parts of filler, 30 parts of type II thixotropic agent sodium bentonite, and 1 part of conductive agent.

[0100] The filler in component A is a mixture of 100 parts by weight of quartz powder, 30 parts by weight of barium sulfate and 4 parts by weight of aluminum oxide. The filler in component B is a mixture of 100 parts by weight of quartz powder and 64 parts by weight of calcium carbonate.

[0101] At -5°C ambient temperature, component A and component B were mixed at a weight ratio of 2:1 and stirred evenly, and poured into the corresponding test mold. The mold was placed in a -5°C to -25°C cycle temperature for curing. The test results of compressive strength and flexural strength are shown in Table 5.

[0102] Example 4.2

[0103] The content of Example 4.2 is basically the same as that of Example 4.1, except that the heating agent described in Example 4.2 is tungsten powder.

[0104] Examples 4.3 to 4.5

[0105] The contents of Examples 4.3 to 4.5 are substantially the same as those of Example 3.1, except that the weight portions of the exothermic agent are 5 parts, 10 parts, and 25 parts, respectively.

[0106] Table 5 Compressive strength and bending strength test results of Examples 4.1 to 4.5 and 3.6

[0107]

[0108] As can be seen from Table 5, the type of heat-generating agent has a significant effect on the results of compressive strength and bending strength. When the same amount of tungsten powder is added, the strength test result of tungsten powder is not as good as that of iron powder. The reason is that the surface of tungsten powder is very easy to oxidize. During the production and feeding process, tungsten powder first reacts with oxygen and moisture in the air to produce redox reaction, so the heat reaction effect is not good. The preferred heat-generating agent is iron powder. When the amount of heat-generating agent is small, the heat provided by the reaction is insufficient, and it is difficult to quickly induce the reaction of the resin and the curing agent, and the strength rises slowly; when the amount of heat-generating agent is large, the oxygen in the mixture is consumed too quickly, the reaction is terminated, and no heat is provided in the later stage, so the later strength changes little; based on the evaluation of cost and effect, the preferred number of heat-generating agents is 20.

[0109] After mixing components A and B in proportion, the heat-generating agent uses the air brought by the mixing process and the moisture and conductive agent brought by component B to generate oxidation heat, inducing the epoxy resin and curing agent to start reacting. After the epoxy resin and curing agent start reacting, the reaction releases heat, which will not only promote their own reaction, but also accelerate the continued dehydration of the Class II thixotropic agent of component B to provide moisture for the heat-generating agent. The heat-generating agent stops reacting until the oxygen inside the mixture is exhausted. After the heat-generating agent reacts, it will become an oxide, increase in volume, occupy the original position of the air, and make the overall structure more compact. In an ultra-low temperature environment, the addition of a self-heating system can significantly increase the reactivity of the splicing adhesive and increase the strength of the splicing adhesive within the same curing time.

[0110] Example 5: Effect of curing agent on the performance of splicing adhesive after adding self-heating system

[0111] Examples 5.1 to 5.5

[0112] A self-heating prefabricated component splicing adhesive is basically the same as Example 4.1, and 20 parts of self-heating agent iron powder are added. The difference lies in the different types of curing agents and the different ratios of component A to component B, as shown in Table 6 for details.

[0113] At an ambient temperature of -5°C, mix component A and component B according to the weight ratio, stir evenly, and pour into the corresponding test mold. Place the mold in a -5°C to -25°C cycle temperature for curing.

[0114] The compressive strength of the prefabricated component splicing adhesive provided by the present invention was measured with reference to T / CECS10080-2020 "Epoxy Adhesive for Prefabricated Segment Assembly". The flexural strength of the prefabricated component splicing adhesive provided by the present invention was measured with reference to GB / T 2567-2021 "Test Method for Properties of Resin Castings". The test results of compressive strength and flexural strength are shown in Table 6, respectively.

[0115] Table 6 Compressive strength and bending strength test results of Examples 5.1 to 5.5 and 4.1

[0116]

[0117] It can be seen from Table 6 that, under ultra-low temperature environment, regardless of the curing agent, the addition of the self-heating system has a significant effect on the improvement of the splicing adhesive reactivity and the rapid growth of strength. After adding the self-heating system, the strength of 1d can meet the requirements of on-site hoisting, and the strength of 14d is close to the final strength, providing a strong guarantee for the safety and stability of prefabricated components.

Claims

1. A self-heating prefabricated component splicing adhesive, characterized in that: The splicing glue is composed of two components A and B which are stored in isolation; The component A is composed of the following raw materials in parts by weight: 80-120 parts of epoxy resin, 1-20 parts of active diluent, 1-10 parts of liquid toughening agent, 5-30 parts of solid toughening agent, 1-10 parts of coupling agent, 50-200 parts of filler, 5-20 parts of heating agent, and 1-5 parts of Class I thixotropic agent; The component B is composed of the following raw materials in parts by weight: 80-120 parts of curing agent, 1-10 parts of accelerator, 10-70 parts of type II thixotropic agent, 0.1-5 parts of conductive agent, and 50-200 parts of filler; The weight ratio of component A to component B is (1-5):1; the heating agent is any one of iron powder and tungsten powder or a mixture of two of them; the Class II thixotropic agent is any one of sodium bentonite and attapulgite or a mixture of two of them, and the moisture content of the Class II thixotropic agent is 10%-20%; the conductive agent is at least one of sodium chloride, potassium chloride, sodium carbonate, and potassium carbonate; the solid toughening agent is any one of ceramic whiskers and inorganic salt whiskers or a mixture of two of them; the ceramic whiskers are at least one of silicon carbide whiskers, potassium titanate whiskers, and aluminum borate whiskers; the inorganic salt whiskers are at least one of calcium sulfate whiskers and calcium carbonate whiskers; the liquid toughening agent is at least one of carboxyl-terminated liquid nitrile rubber, liquid polysulfide rubber, and hydroxyl-terminated liquid silicone rubber.

2. The splicing adhesive according to claim 1, characterized in that: The component A is composed of the following raw materials in parts by weight: 100 parts of epoxy resin, 10 parts of active diluent, 5 parts of liquid toughening agent, 25 parts of solid toughening agent, 3 parts of coupling agent, 134 parts of filler, 20 parts of exothermic agent, and 3 parts of Class I thixotropic agent.

3. The splicing adhesive according to claim 1, characterized in that: The component B is composed of the following raw materials in parts by weight: 100 parts of curing agent, 5 parts of accelerator, 30 parts of type II thixotropic agent, 1 part of conductive agent, and 164 parts of filler.

4. The splicing adhesive according to claim 1 or 2, characterized in that: The active diluent is at least one of butyl glycidyl ether, 1,4-butanediol diglycidyl ether, benzyl glycidyl ether, dodecadecyl glycidyl ether, and 1,6-hexanediol diglycidyl ether; and the type I thixotropic agent is hydrophobic fumed silica.

5. The method for preparing the splicing adhesive according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step (1), preparation of component A: mixing epoxy resin, reactive diluent and liquid toughening agent evenly; adding filler, solid toughening agent and coupling agent, and stirring in vacuum; adding exothermic agent and Class I thixotropic agent, stirring evenly, obtaining component A and storing separately; Step (2), preparation of component B: mix the curing agent and the accelerator evenly; add the filler and the conductive agent, and stir in a vacuum; add the type II thixotropic agent, stir evenly, obtain component B and store it separately; Step (3), when in use, mix component A and component B evenly to obtain the splicing glue.

Citation Information

Patent Citations

  • Room-temperature-curing ultralow-temperature-resistant epoxy adhesive and preparation method thereof

    CN117551409A

  • Composite plate pre-embedding adhesive and preparation method thereof

    CN107779148A